2017
DOI: 10.1186/s12985-017-0892-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative epidemiology of porcine circovirus type 3 in pigs with different clinical presentations

Abstract: BackgroundPorcine circovirus type 3 (PCV3), as an emerging circovirus species, was reported to be widely circulating in the United States, China, South Korea and Poland. Previous studies revealed that PCV3 was mainly concentrated in sick animals with respiratory disease, skin disease, reproductive disorders and so on. However, the circulating status of PCV3 in pigs with other clinical presentations (especilly asymptomatic or diarrhea) was not well established.FindingsIn this study, to conduct a comparative epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 22 publications
9
109
3
1
Order By: Relevance
“…In the present study, PCV3 was detected in samples from pigs with different clinical presentations, and the PCV3‐positive rates were different for different clinical presentations, showing rates of 73.33% (11/15), 46.15% (12/26), 27.78% (10/36), 23.38% (18/77), 13.33% (2/15) and 0% (0/1) for PDNS, sows who underwent abortions and stillbirths, diarrhoea, PMWS, respiratory symptoms and piglets with neurological symptoms, respectively. The results showed that there was a higher PCV3 detection rate in samples from pigs with diarrhoea, which is similar to results reported previously (Zhai et al., ; Wang, Zhang, Zhang et al., ), suggesting PCV3 might have a potential association with swine diarrhoea. Furthermore, PCV3 and PEDV were simultaneously detected by our group in diarrhoeal samples in another study (data not shown).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, PCV3 was detected in samples from pigs with different clinical presentations, and the PCV3‐positive rates were different for different clinical presentations, showing rates of 73.33% (11/15), 46.15% (12/26), 27.78% (10/36), 23.38% (18/77), 13.33% (2/15) and 0% (0/1) for PDNS, sows who underwent abortions and stillbirths, diarrhoea, PMWS, respiratory symptoms and piglets with neurological symptoms, respectively. The results showed that there was a higher PCV3 detection rate in samples from pigs with diarrhoea, which is similar to results reported previously (Zhai et al., ; Wang, Zhang, Zhang et al., ), suggesting PCV3 might have a potential association with swine diarrhoea. Furthermore, PCV3 and PEDV were simultaneously detected by our group in diarrhoeal samples in another study (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…The cap protein determines the antigenic characteristics of circoviruses (Nawagitgul et al., ); however, the cap protein of PCV3 shares only approximately 37% identity with that of PCV2. To date, PCV3 has been detected throughout commercial pig farms from 21 provinces or districts (i.e., Guangdong, Guangxi, Anhui, Chongqing, Fujian, Hebei, Henan, Hunan, Hubei, Jiangsu, Jiangxi, Liaoning, Shenyang, Jinlin, Zhejiang, Shandong, Gansu, Neimenggu, Beijing, Sichuan and Yunnan) in China (Fan et al., ; Fu et al., ; Ku et al., ; Zhai et al., ; Zhang, Luo, Liang, Li, & Cui, ). Therefore, this study aimed to investigate the occurrence of PCV3 DNA and its genetic characteristics, using tissue and serum samples from 41 pig farms in 14 cities in central China, from 2013 to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies identified the presence of PCV‐3 in several tissue samples or sera from pigs with different clinical presentations (Palinski et al., ; Tochetto et al., ; Zhai et al., ), as well as in healthy animals (Franzo, Legnardi, Hjulsager et al., ; Franzo, Legnardi, Centelleghe et al., ; Zheng et al., ). The data compiled in this study suggest a homogeneous PCV‐3 frequency in the different production phases and clinical/pathological conditions, as no statistically significant differences were found among tested groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhai et al. () found lower qPCR Ct values in samples from animals with respiratory signs and diarrhoea compared to those of asymptomatic animals, suggesting that PCV‐3 may be potentially associated with these clinical conditions. A recently described qPCR for PCV‐3 detection (Franzo, Legnardi, Centelleghe et al., ) was attempted in the present study with a limited number of positive samples as an exploratory approach (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation